2008
DOI: 10.1002/ab.20251
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence that specific candidate genes are associated with adolescent‐onset antisocial behavior

Abstract: Though initially conceptualized as resulting from peer imitation of child-onset or life-course-persistent youth [Moffitt, 1993], there is mounting evidence from twin studies that adolescent-onset or adolescent-limited antisocial behavior may also be genetically influenced. This study sought to provide preliminary molecular genetic evidence in support of these findings. We further evaluated whether genetic associations varied between behavioral subtypes of ASB (i.e., physical aggression and nonaggressive rule-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 38 publications
4
71
0
3
Order By: Relevance
“…Specifically, physical aggression appears to be more heritable than rule-breaking (i.e., genetic influences account for 65 and 48% of the variance, respectively), whereas rule-breaking is influenced more by the shared environment than is aggression (i.e., shared environmental influences account for 5 and 18% of the variance, respectively) [Burt, 2009;Tackett et al, 2005]. Recent work has also suggested that associations with particular candidate genes (namely, 5HT 2A His452Tyr and DAT1) vary across physical aggression and rule-breaking [Burt and Mikolajewski, 2008], such that these particular genes are uniquely associated with rule-breaking. In short, there is converging evidence that physical aggression and nonaggressive, rule-breaking constitute two separable though correlated subtypes of antisocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, physical aggression appears to be more heritable than rule-breaking (i.e., genetic influences account for 65 and 48% of the variance, respectively), whereas rule-breaking is influenced more by the shared environment than is aggression (i.e., shared environmental influences account for 5 and 18% of the variance, respectively) [Burt, 2009;Tackett et al, 2005]. Recent work has also suggested that associations with particular candidate genes (namely, 5HT 2A His452Tyr and DAT1) vary across physical aggression and rule-breaking [Burt and Mikolajewski, 2008], such that these particular genes are uniquely associated with rule-breaking. In short, there is converging evidence that physical aggression and nonaggressive, rule-breaking constitute two separable though correlated subtypes of antisocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…the linear increase of occurrence of 10/10 genotypes with the increase of sportive achievements in shooting. Interestingly, the 10/10 DAT1 genotype had been associated with antisocial behavior in adolescents [31], as well as with aggression and delinquency [33].…”
Section: Resultsmentioning
confidence: 99%
“…Nessa categoria, foram considerados os estudos que abordam as influências genéticas possivelmente relacionadas com o desenvolvimento de comportamentos antissociais (Burt & Mikolajewski, 2008;Silberg, Rutter, Tracy, Maes, & Eaves, 2007). O estudo de Silberg et al (2007), por exemplo, identificou que os comportamentos antissociais podem ser hereditários nos casos da antissocialidade persistente -ALV -e que, por outro lado, mudanças biológicas típicas da puberdade, envolvendo aspectos hormonais e o crescimento do corpo, podem estar associadas à ALA. Os autores afirmam que, apesar de existirem influências genéticas, devem ser consideradas as fases do desenvolvimento do indivíduo e as influências ambientais, pois os comportamentos antissociais têm causas multifatoriais (Silberg et al, 2007).…”
Section: Influências Genéticasunclassified
“…No entanto, é necessário perceber que existem diversos fatores de risco que podem desencadear os comportamentos antissociais e deve-se levar em consideração o contexto em que esse indivíduo está inserido a fim de evitar o reducionismo e o determinismo, pois cada indivíduo age de forma singular aos eventos que enfrenta ao longo do desenvolvimento (Burt, 2008). Assim, cada caso deve ser estudado de forma diferenciada e deve-se levar em conta a fase do desenvolvimento do indivíduo.…”
Section: Considerações Finaisunclassified